The differences between top senior basketball players with different situation efficacy in relation to conative characteristics - Sindik, J.; Vukosav, J. (Facta Universitatis: Series Physical Education and Sport, 2011)
The assessment of differences in psychological characteristics between players of different levels of success may contribute to a better understanding of the basketball players' overall situation efficacy. Our research was aimed at ascertaining the differences between extreme groups of top Croatian senior basketball players, with either best or lowest situation efficacy. The final sample of subjects (60 basketball players with the lowest and the highest total situation efficacy) was selected from the initial sample of 107 subjects, basketball players from nine men senior teams from the A-1 Croatian Men Basketball League during the 2006/2007 championship season. The players with the best situation efficacy and those with the lowest situation efficacy cannot be statistically significantly distinguished on the basis of the group of conative characteristics and perceived group cohesion, therefore the research hypothesis has been rejected.